Algebra Adventure – An Application to Learn Algebra through Gamification Approach - Mohd Yusoff, Nur Atika Shafika; Suparjoh, Suriawati (Applied Information Technology And Computer Science, 2021)
Mathematics is a challenging topic, particularly Algebra, since it involves calculations with the alphabets, numbers, and operations such as power. The major goals of this application are to use a PC gamification technique to help kids comprehend math better. This is where Algebra Adventure: PC Game for Learning Algebra comes in handy. Direct questions and problem solving are the two types of questions available in this application. Students will be able to answer the questions via this application. This allows students to have a better understanding of the subject while also forcing them to think about how to solve the challenges